The Relationship between Dimensions of Organizational Culture and Organizational Effectiveness: A Systematic Literature Review - Marlius, Doni; Rino, Rino (UNIVERSITAS PAKUAN, 2025)
This study examines the relationship between organizational culture dimensions and organizational effectiveness through a systematic literature review. The study identifies various dimensions of organizational culture that contribute significantly to improving organizational effectiveness, including shared values, norms, attitudes, and organizational practices. Through an analysis of recent empirical and theoretical studies, it is found that a strong and positive culture supports the achievement of organizational goals by improving employee performance, job satisfaction, and commitment. This study highlights the importance of understanding organizational culture as a key variable in managing change and improving effectiveness across various organizational contexts. These findings provide practical implications for managers and researchers in developing cultural strategies that support long-term organizational success.